Modifying “Hide And Seek” Traditional Game to Teach Vocabulary for Early Childhood Students - Rochyani Lestiyanawati (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2017)
As the importance of English in this globalization era, it is taught in all level of education program, including for early childhood education as extracurricular program. Meanwhile, the fastest spreading of technology also influences children, impacting on the overuse of gadget for children. The children nowadays are busy playing with their smartphone and avoid playing traditional games. Consequently, the nature of educative values on traditional games are decrease significantly. Dealing with such problem, the needs for a method of teaching English as well as giving students motivation to preserve the existence of traditional games is unavoidable. In this paper, the writer aimed to introduce a concept of teaching English vocabulary for early childhood students by using ‘hide and seek’ traditional games. The modification of the traditional game in teaching English is to give another way of creating an enjoyable teaching and learning process for early childhood students. Through games, the teachers are able to create a various context for students to learn and play as well. This paper is to bring another model for teachers to deal with the importance of English and the conservation of traditional games in teaching process.